Jaundice due to cephalopancreatic neoplasm.: Cómo disminuir la mortalidad operatoria de las intervenciones quirúrgicas paliativas. - Tiscornia, Eduardo; Delgado, Alicia (Cirugía del Uruguay, 1988)
High mortality follows palliative operations in pa• tients with pancreatic neoplasm.